Novo modelo animal de lesão por extravasamento induzida por Vinorelbina: estudo dos mecanismos patogênicos como potenciais alvos terapêuticos - Quintela, Lizias Claudia Sampaio (2023)
Extravasation injury is a term that describes the manifestations of tissue damage resulting from the accidental leakage of a drug into the subcutaneous space during intravenous infusions. Vinca alkaloids and their derivatives, such as vinorelbine, are among the most prominent vesicant anticancer drugs. We aimed to design an experimental model of vinorelbine-induced extravasation injury and test the role of resident cells in the injury mechanism. Male Wistar rats were divided into groups (n=6/group). Anesthetized animals received an intradermal injection of saline solution (control group, 100l /site) or vinorelbine (0.03, 0.1, 0.3, or 1 mg/100 l /site). The animals were euthanized after 2, 4, 8, or 16 h after chemotherapy injection. Skin samples were analyzed by the myeloperoxidase (MPO) assay to determine the time course of inflammation. The experiment was repeated following the same time course using the Evans blue dye extravasation method to determine cutaneous vascular permeability. The dye (25 mg/kg, i.v.) was administered one h before the euthanasia of the animals. Tissue samples were analyzed histopathologically to analyze the damage caused by vinorelbine and to establish a histo-score for grading the lesion. Subsequently, an immunofluorescence assay was developed in skin samples to evaluate the expression of iNOS and TNF-α. In another experimental context, the animals were divided into two groups: rats with peritoneal cavities washed with saline solution and rats with unwashed peritoneal cavities. These groups received saline (1 ml/well, i.p.), vinorelbine (1 mg/ml/well, i.p.), or vinorelbine + dexamethasone (3 mg/kg, s.c.) 30 min after lavage. The peritoneal exudate was collected four h after chemotherapy exposure to measure the number of migrated neutrophils. The highest concentration of vinorelbine tested (1 mg/site) caused an increase in the accumulation of neutrophils in the longest time tested, that is, 16h. This finding was accompanied by a time-dependent edematogenic response, detected by cutaneous vascular permeability to Evans blue at 16 hours after exposure to chemotherapy compared to the saline group (P < 0.05). Vinorelbine did not induce signs of inflammation at 2, 4, or 8 hours after drug injection. The histoscore standardized in this study showed an intense pattern of injury associated with vinorelbine when extravasated into the tissue (scores 9[8–9]). These damages were attenuated (P<0.05) when previously using dexamethasone (scores 7.5[7– 8]). Vinorelbine induced iNOS expression, but not TNFα, in skin samples injected with vinorelbine, which was reduced by dexamethasone. In the resident cell depletion assay, a reduction in the population of mononuclear cells was observed in the peritoneal cavity of rats after peritoneal lavage with saline solution. The capacity of vinorelbine to induce the accumulation of neutrophils was enhanced in the washed cavity, suggesting the independence of resident cells in the inflammatory capacity of the chemotherapy agent. Dexamethasone significantly prevented neutrophil migration (P<0.05), indicating that vinorelbine induces neutrophil chemotaxis in a mechanism independent of resident cells but dependent on inflammatory chemical mechanisms of protein nature. Thus, we designed a new animal model of vinorelbine-induced extravasation injury. Additionally, we developed a standardized histo- score grading system for lesion assessment. The chemotherapeutic induced the accumulation of neutrophils during tissue injury regardless of stimulation of resident cells.